AI Technologies and Virtual Reality Proceedings of 7th International Conference on Artificial Intelligence and Virtual Reality (AIVR 2023) - Nakamatsu, Kazumi; Patnaik, Srikanta; Kountchev, Roumen (Smart Innovation, Systems and Technologies, 2024)
XVI, 454 p. 193 illus., 165 illus. in color.